Áreas de intensa agropecuária podem apresentar comunidades de anuros representativas? - Ramos, Jade (2011)
The attributes that make amphibians good environmental indicators are permeable skin, shell-less eggs and life cycle with two phases in most of the species, one terrestrial (adult) and other aquatic (tadpoles). Moreover, they are important components of many ecological communities, either by eating a multitude of insects or serving as prey for other animals. Currently many species have suffered population declines or have become extinct. The hypotheses tested were: (a) water bodies in the southwest region of Goiás do not show species richness similar to other regions of the Cerrado biome; (b) the structural integrity (measured by environmental integrity index) of the water body interferes with richness and abundance of the anuran species found; (c) water bodies located in preserved areas show higher species richness, abundance of individuals and β diversity than anthropized water bodies (located in pasture, soy and sugar-cane fields). Field observations were conducted between 2009 and 2010 in six municipalities in southwest Goiás: Aporé, Jataí, Mineiros, Portelândia, Rio Verde and Serranópolis. Forty-three water bodies were sampled, being ten of them found in sugar cane crops, twelve in pasture, twelve in soybean crops and nine in areas of natural vegetation. We recorded 34 species of frogs. Considering all water bodies sampled in southwest Goiás, both collector’s curves made with the occurrences of tadpoles and adults tended to stabilize. The richness estimated for adults was 39.89 ± 5.06 and 35.82 ± 7.62 for tadpoles. The most abundant species in adult stage were Dendropsophus cruzi, D. minutus and Hypsiboas albopunctatus, respectively, while in larval stage the most abundant were Hypsiboas albopunctatus, Physalaemus cuvieri and Scinax fuscovarius. Overall, for both adults and tadpoles, we found no correlations between richness and abundance of species and environmental integrity index for any of the four types of water bodies. The only exception was when species abundance (adult phase) was related to the environmental integrity index of all water bodies. The species composition (adult and larval stage) did not differ among the types of water bodies. All hypotheses tested were rejected. Although the southwest Goiás is impacted by agriculture, the anuran species richness is similar to other areas of Cerrado.